Host-parasite relationship of Ortholinea lauquen sp. nov. (Cnidaria: Myxozoa) and the fish Galaxias maculatus in northwestern Patagonia, Argentina - Alama Bermejo, Gema (2019)
Galaxias maculatus (Jenyns, 1842) is a widespread freshwater fish and an important component of the economically important whitebait fisheries across the Southern Hemisphere. We report a new myxosporean parasite (Cnidaria: Myxozoa) infecting the kidney of G. maculatus from northwestern Patagonia (Argentina). Ortholinea lauquen sp. nov. was characterized using myxospore morphology, morphometrics and small subunit rDNA (ssrDNA) sequence data. Our ssrDNA phylogenetic analyses showed that O. lauquen sp. nov. is a member of the oligochaete-freshwater urinary tract clade and basal to a clade containing 4 different spore morphotypes (Chloromyxum, Myxidium, Zschokkella, Hoferellus). We explored host-parasite relationships at the macro- and microscale by analyzing the distribution, tissue tropism and pathology of O. lauquen sp. nov. Prevalence was relatively low (7%) by microscopy, but PCR detection revealed hidden levels of infection (49%), with the highest detection in lakes Morenito and Moreno (63-90%, Río Negro Province). The only locality negative by both microscopy and PCR was the Caleufu River (Neuquén Province), suggesting differences in fish life history traits (landlocked vs. potamodromous) or preference of the putative obligate invertebrate host for lentic habitats. O. lauquen sp. nov. sporulates in the renal tubules and occasionally in the glomerular space. The plasmodia frequently occluded the tubule lumina, and cellular necrosis and disintegration of the epithelium were observed. O. lauquen sp. nov. could represent a potential threat to G. maculatus culture under intensive farming conditions.